2021
DOI: 10.1080/03019233.2020.1869411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce on inclusion evolution and HAZ mechanical properties of Al-killed high-strength steel

Abstract: The effect of Ce on inclusion evolution behaviour in 700 MPa class Al-killed high-strength steel was investigated through experimental observations and thermodynamic calculations. Simulated welding experiments and mechanical characterisation tests of the heat-affected zone (HAZ) were also carried out to investigate the effect of adding Ce on the welding performance. The results reveal that the typical inclusions of Ce-free steel are the CaS + Mg-Al-O + Ti(C,N) complex inclusion and isolated CaS inclusion. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Materials 2022, 15, x FOR PEER REVIEW 13 of 18 [92] analyzed the influence of Ce on the precipitation of inclusions in 700 MPa high strength steel and the properties of HAZ and found that RE and RE inclusions in Ce containing steel could also pin austenite grain boundaries, improve the crack propagation resistance of HAZ, and increase the mechanical properties, as shown in Figure 11. Therefore, the characteristics that RE and RE inclusions affecting the upper bainite transformation, refining the martensite lath and the austenite grain, and pinning the grain boundary can be used to reduce the brittle structure of HAZ.…”
Section: Effect Of Re On Weldability In High Strength Steel With High...mentioning
confidence: 99%
“…Materials 2022, 15, x FOR PEER REVIEW 13 of 18 [92] analyzed the influence of Ce on the precipitation of inclusions in 700 MPa high strength steel and the properties of HAZ and found that RE and RE inclusions in Ce containing steel could also pin austenite grain boundaries, improve the crack propagation resistance of HAZ, and increase the mechanical properties, as shown in Figure 11. Therefore, the characteristics that RE and RE inclusions affecting the upper bainite transformation, refining the martensite lath and the austenite grain, and pinning the grain boundary can be used to reduce the brittle structure of HAZ.…”
Section: Effect Of Re On Weldability In High Strength Steel With High...mentioning
confidence: 99%
“…These particles are dispersed relatively even in the matrix, which can avoid large stress concentration around inclusions and improve the toughness of steel. [14,15] Geng et al [16] discussed the effects of Ce on heat affected zone (HAZ) mechanical properties of Al-killed high-strength steel. The results showed that the number density of inclusions increases, and the average size of inclusions decreases after adding Ce.…”
Section: Introductionmentioning
confidence: 99%
“…The type, quantity, size, and distribution of inclusions have been found to significantly affect the properties [7][8][9][10] and localized corrosion of steel. [11,12] The mechanism of pitting corrosion induced by inclusions has been analyzed by many researchers.…”
Section: Introductionmentioning
confidence: 99%